The Female Trinity: Virgin, Mother, and Whore - Dedees, Adek Risma (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2023)
From the title, Akhir Penjantanan Dunia, this book seems heroic and obsessive about ending the oppressive ideology of patriarchy. And it is okay if it is also a marketing gimmick. There is mounting anger not only from the topic being discussed but also from the choice of words that are strong, straightforward, and, of course, critical (isn't this characteristic of feminist writers?). The author also mentions the matriarchal social system in human culture, such as in Minangkabau, West Sumatra, but, unfortunately, it is not discussed in more depth how this system works as a system that is not as oppressive as the patriarchate. Even so, this book presents many "flesh" arguments that need to be read by researchers of gender issues.